‘So they do not profit this people at all’ (Jr 23:32): A critique of prophecy - Wessels, Willie (Verbum et ecclesia, 2011)
Jeremiah 23:9-40 is a section of the Bible that is dedicated to the issue of true and false prophets. This section follows the cycle of the kings in Jeremiah 21:1-23:8. Both these cycles form part of an editorial unit 21:1-24:10. The kings and the prophets, along with the priests constituted the leadership in Israelite society. The view presented in 21:1-23:40 is that of a failed leadership and the result was the Babylonian exile. In this article the focus is on the prophets who are regarded as false. Jeremiah 23:9-40 is a collection of oracles ascribed to Jeremiah by tradition. In most instances the oracles are of a general nature and lack contextual concreteness. The literary context created by the compilers of 21:1-23:40 is essential to the argument presented in this article. According to Jeremiah 23:32 the false prophets ‘… do not profit the people at all’ (New Revised Standard Version of the Bible [NRSV]). The line of reasoning in this article will be that, as religious leaders, prophets should benefit the people. In the context of 21:1-23:40 they had failed to do this. If the prophets had been in proper communication with Yahweh, they would not have misled the people. From the point of view of the collectors, most probably in an exilic context, the message is clear: the prophets have failed the people, the exile is a reality, and there is no longer any room for false prophets. Jeremiah 23:25-32 makes it clear that, if prophetic words do not profit Yahweh’s people, they should be regarded as false and misleading.The passage for discussion in this article is Jeremiah 23:25-32. The very last sentence in this passage (v. 32) seems to be the culminating point of the complaint against the opposing prophets: ‘so they do not profit this people at all’. The purpose of this article is to address this issue of prophets benefiting the ordinary people. From this final sentence one can conclude that one of the marks of a true prophet is that ordinary people should benefit from his performance as a prophet. The question will be, ‘What can a prophet contribute to society that will benefit the people?’ If we ask this question in the current context, the highlighting of the negative aspect of the prophets will guide us to what the expectation of the writer (prophet) was. Prophets, according to the classical definition of their function, are supposed to communicate to people the messages they receive from Yahweh (Redditt 2008:6; cf. also Blenkinsopp 1996:28-30).1 In verse 28 of the passage under discussion Yahweh says: ‘… let the one who has my word speak my word faithfully’ (NRSV). The role of the prophets is to act as channels of communication between Yahweh and the people. Yahweh sends his messages to his covenant people through the prophets he has commissioned for this purpose.